Procalcitonin levels in preterm newborns: Reference ranges during the first three days of life - Tuoni, Cristina; Ciantelli, Massimiliano; Morganti, Riccardo; Violi, Martina; Tamagnini, Sara; Filippi, Luca (Frontiers in Pediatrics, 2022)
Background: sepsis is one of the most important causes of morbidity and mortality in neonatal period, especially in preterms. Diagnosis is difficult because of aspecific signs and symptoms. Diagnostic gold standard is blood culture but its sensibility is low. Much effort has been made to identify early, sensitive and specific diagnostic markers; among these particular attention was paid to procalcitonin. However, reference ranges of serum PCT shortly after birth haven’t been sufficiently studied in healthy preterms and literature is still contradictory. Objectives: the aim of the study is to define PCT age specific reference ranges in the first 72 hours of life in uninfected VLBW preterms. Methods: serum levels of PCT were assessed for each newborn at birth and every 24 hours until the third day of life. The eligible patients were classified into two groups according to their sepsis status. Results: 343 patients were enrolled; 28 were septic and 315 non-septic. In non-septic infants were performed 1015 determinations of PCT values. Our data showed a trend in average value of PCT to increase after birth up to a peak between 24 and 48 hours of life and subsequently to fall. The average peak value was 15.12 ng/ml achieved at nearly 36 hours of life. Conclusions: Our study shows a PCT nomogram of healthy preterms which is different from the one of term newborns. Data agree with what is reported in literature regarding the reference ranges and trends of PCT in non‐septic preterms shortly after birth.